2007
DOI: 10.1248/yakushi.127.375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-dose Milrinone on Weaning from Cardiopulmonary Bypass and after in Patients with Mitral Stenosis and Pulmonary Hypertension

Abstract: The phosphodiesterase inhibitor milrinone is usually preferred in patients with pulmonary hypertension and myocardial dysfunction after cardiopulmonary bypass. We investigated the eŠects of low-dose milrinone on pulmonary hypertension in the immediate pre-and postoperative period. Forty-seven patients were randomized to the control and milrinone groups. All patients had mean pulmonary artery pressure greater than 30 mmHg and pulmonary capillary wedge pressure greater than 20 mmHg and were candidates for mitral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…They are most suited to short-term use because of tachyphylaxis [159], and mild tachycardia is common. Milrinone is most frequently used and has been shown to reduce pulmonary pressures and augment RV function in many studies in patients with pulmonary vascular dysfunction [160-164]. Enoximone improves RV function in pulmonary vascular dysfunction after cardiac surgery [165,166] and in patients with decompensated chronic obstructive pulmonary disease (COPD) [167].…”
Section: Resultsmentioning
confidence: 99%
“…They are most suited to short-term use because of tachyphylaxis [159], and mild tachycardia is common. Milrinone is most frequently used and has been shown to reduce pulmonary pressures and augment RV function in many studies in patients with pulmonary vascular dysfunction [160-164]. Enoximone improves RV function in pulmonary vascular dysfunction after cardiac surgery [165,166] and in patients with decompensated chronic obstructive pulmonary disease (COPD) [167].…”
Section: Resultsmentioning
confidence: 99%
“…Milrinone is frequently the agent of choice in patients with pulmonary hypertension from biventricular failure, and in those recovering after ventricular assist or cardiac transplantation (90)(91)(92). Several small studies have also examined the use of inhaled milrinone in patients with pulmonary vascular disease to avoid systemic hypotension (93)(94)(95)(96).…”
Section: Focused Reviewmentioning
confidence: 99%
“…Only a couple of studies have previously examined milrinone in pulmonary hypertension occurring during mitral valve surgery. Oztekin et al [16] reported that using milrinone caused significant reduction in pulmonary artery pressure, central venous pressure and pulmonary capillary wedge pressure in patients with mitral valve stenosis and PHT undergoing mitral valve replacement. They also found that it facilitated weaning from cardiopulmonary bypass with less side effects.…”
Section: Discussionmentioning
confidence: 99%